Positive view and increased likely uptake of follow‐up testing with analysis of cell‐free fetal DNA as alternative to invasive testing among Danish pregnant women. (15th February 2018) - Miltoft, Caroline B.; Rode, Line; Tabor, Ann
Abstract: Introduction: The aim of this study was to investigate the attitude (view, likely uptake and preferred strategy) towards cell‐free fetal DNA (cfDNA) testing among pregnant women before a first‐trimester risk assessment for trisomy 21 (unselected women) and after obtaining a high risk. Material and methods: Unselected and high‐risk women attending first‐trimester screening (Rigshospitalet, Copenhagen University Hospital) were invited to fill out the questionnaire Antenatal testing for Down syndrome as an online survey. Results: The survey included 203 unselected and 50 high‐risk women (response rates of 74.8% and 84.7%, respectively). Nearly all considered cfDNA testing a positive development in antenatal care, and 97.2% would like it to be offered. Offering cfDNA testing as an alternative to invasive testing would increase the uptake of follow‐up testing compared with invasive testing alone (98.8% vs. 90.7%, p < 0.001). Women who would only accept follow up by cfDNA testing were more likely to continue an affected pregnancy (30.0% vs. 3.6%, p < 0.001) or have doubts about termination (50.0% vs. 32.1%, p < 0.001). Conclusions: Offering cfDNA testing would likely increase the uptake of follow‐up testing without a corresponding rise in the termination rate of affected fetuses as some women test for information only. However, both unselected and high‐risk women had overwhelmingly positive views underlining attention to avoid routinization.